Elevation of Serum Thrombopoietin Precedes Thrombocytosis in Kawasaki Disease - Ishiguro, Akira; Ishikita, Takashi; Shimbo, Toshikazu; Matsubara, Kousaku; Baba, Kunizou; Hayashi, Yasuhide; Naritaka, Shin-ichi; Nakahata, Tatsutoshi (Thrombosis and Haemostasis, 1998)
Kawasaki disease (KD) is an acute systemic vasculitis causing coronary arterial aneurysms and myocardial infarction in young children. Prominent thrombocytosis with increased megakaryocytes develops during the convalescent period. To clarify the mechanisms of thrombocytosis, we studied serum levels of thrombopoietin (TPO) and other thrombopoietic cytokines in 40 patients with KD (149 samples) and 106 age-matched controls using ELISA. TPO values in the controls were 1.94 ± 0.69 fmol/ml (mean ± SD) with a 95% reference interval of 0.85 to 3.27 fmol/ml. In the first week of KD, platelet counts were normal but TPO values increased (~ 15.5 fmol/ml). TPO levels peaked on day 6 ± 2 at 5.94 ± 2.64 fmol/ml and then fell gradually. When platelet counts peaked in the second to third weeks, TPO levels were still high or comparable with the controls. TPO levels in KD patients with normal platelet counts were significantly higher than control levels. Interleukin (IL)-6 levels in the first week rose, but neither IL-11 nor leukemia inhibitory factor was detectable. These results suggest that TPO contributes to thrombocytosis in KD in conjunction with IL-6 and TPO production may be enhanced during the acute phase.